Volatile Metabolism of Wine Grape Trincadeira: Impact of Infection with Botrytis cinerea - Helena Santos; Catarina Augusto; Pedro Reis; Cecília Rego; Ana Cristina Figueiredo; Ana Margarida Fortes (Plants, 2022)
The aroma of grapes is cultivar dependent and is influenced by terroir, vineyard practices, and abiotic and biotic stresses. Trincadeira is a non-aromatic variety associated with low phenolic content and high sugar and organic acid levels. This cultivar, widely used in Portuguese wines, presents high susceptibility to Botrytis cinerea. This work aimed to characterise the volatile profile of Trincadeira grapes and how it changes under infection with B. cinerea. Thirty-six volatile organic compounds were identified, from different functional groups, namely alcohols, ester acetates, fatty acid esters, fatty acids, aldehydes, and products of the lipoxygenase pathway. Both free and glycosidic volatile organic compounds were analysed by Gas Chromatography and Gas Chromatography coupled to Mass Spectrometry for component quantification and identification, respectively. A multivariance analysis showed a clear discrimination between healthy and infected grapes with 2-trans-hexenal and isoamyl-acetate among the compounds identified as negative and positive markers of infection, respectively. Ester acetates such as 2-phenylethyl acetate, isoamyl acetate, and 2-methylbutyl acetate were present in higher contents in infected samples, whereas the contents of several fatty acid esters, such as ethyl decanoate and ethyl dodecanoate, decreased. These data were integrated with quantitative PCR data regarding genes involved in volatile metabolism and showed up-regulation of a gene coding for Hydroperoxide Lyase 2 in infected grapes. Altogether, these changes in volatile metabolism indicate an impact on the grape quality and may be related to defence against B. cinerea. The presence/absence of specific compounds might be used as infection biomarkers in the assessment of Trincadeira grapes’ quality.